PENINGKATAN LEARNING ORGANIZATION MELALUI KEPEMIMPINAN TRANSFORMASIONAL DAN EFIKASI DIRI GURU SMP SWASTA BUDDHIS SE-PROVINSI BANTEN - Hendri Ardianto; Widodo Sunaryo; Sumardi . (JURNAL MANAJEMEN PENDIDIKAN, 2020)
IMPROVEMENT OF LEARNING ORGANIZATION THROUGH TRANSFORMATIONAL LEADERSHIP AND EFICATION OF TEACHER OF BUDDHIS PRIVATE SCHOOL BANTEN PROVINCEThe purpose of this study was to find that learning organization can be improved by examining the relationship of learning organization, transformational leadership and self-efficacy. This research was conducted with a quantitative approach by using correlational statistical methods to determine whether transformational leadership and self-efficacy have a positive relationship with learning organization. Sampling in this study was using proportional random sampling technique with the taro yamane formula. The data collection to measuring instruments was a questionnaire. The results were continually analyzed by using the SITOREM methods in order to derive recommendations and determine the order of priority improvements that need to be made. This research was conducted on Buddhist Private Middle School teachers in Banten Province with a study population of 145 and a sample of 107 teachers. The results showed that there was a positive relationship between transformational leadership and learning organization with a relationship strength of ry1 = 0,530 and there was a positive relationship between self-efficacy and learning organization with a strength of ry2 = 0,477. This shows that learning organizations can be improved through the development of transformational leadership and self-efficacy. Sitorem’s analysis results showed that in the components of transformational leadership, self-efficacy and learning organization were found 10 indicators that need to be improved, namely: 1) Individualized consideration, 2) Confidence in understanding his / her abilities, 3) commitment and determination of everyone in the organization, 4) Systematic thinking patterns, 5) Individual Skills, 6) Organizational team attitude, 7) Make generalizations, 8) A conception of an ideal future, 9) A vision which agreed upon by all members of the organization and 10) Maturity.